2023
DOI: 10.1002/app.54720
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of starch biofilm reinforced with cellulose microfibers isolated from Musa Saba' midrib residue and its application as an active packaging film

Dayangku Nurshahirah Awang Wahab,
Md. Bazlul Mobin Siddique,
Jiuan Jing Chew
et al.

Abstract: Two main disadvantages of starch‐based biofilms are their low mechanical strength and high hydrophobicity. This work investigated incorporation of cellulose microfibers (CMF) with a range of CMF loading (i.e., 0, 0.5, and 1.0 wt% of CMF) as fillers to improve the mechanical properties of starch‐based biofilm. CMFs (average diameter = 75 μm) were isolated from midrib of Musa Saba' banana residue using chemical treatments of steam explosion alkaline treatment, acid‐chlorite treatment, and acid hydrolysis. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(154 reference statements)
0
0
0
Order By: Relevance
“…The thickness of starch/MCC films slightly increased with increasing MCC contents in the films. The observed increase in thickness of starch/MCC films with rising MCC contents is in line with previous findings, such as those reported by Wahab et al (2023) [36]. They found that the addition of 1% (w/w) MCC extracted from banana (Musa Saba) midrib residues increased the thickness of wheat starch films from 165 to 181 µm.…”
Section: Appearances and Thicknesssupporting
confidence: 92%
“…The thickness of starch/MCC films slightly increased with increasing MCC contents in the films. The observed increase in thickness of starch/MCC films with rising MCC contents is in line with previous findings, such as those reported by Wahab et al (2023) [36]. They found that the addition of 1% (w/w) MCC extracted from banana (Musa Saba) midrib residues increased the thickness of wheat starch films from 165 to 181 µm.…”
Section: Appearances and Thicknesssupporting
confidence: 92%